2011
DOI: 10.1103/physrevb.84.085411
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the orthorhombic Al13Co4(100) surface using LEED, STM, andab initiostudies

Abstract: In a combined scanning tunneling microscopy (STM), low-energy electron diffraction (LEED) and density functional theory (DFT) study of the surface of Al 13 Co 4 (100), all techniques have found that after annealing to 1165 K, the surface structure is consistent with a dense Al-rich plane with surface Co atom depletion. Various structure models were considered, and in the LEED study, the best agreement was found with a model that consists of Al-rich terminating planes with no Co atoms, and otherwise a struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 31 publications
9
60
1
Order By: Relevance
“…Earlier studies of the (100) surface based on both experimental (STM, XPS, and dynamical LEED) and ab initio studies using density functional theory (DFT) have shown that the surface terminates at incomplete P layers. 16,17 The best agreement is found for the P termination models that have all 22 Al atoms per surface unit cell present, but with all 4 Co atoms per unit cell missing. Aside from these missing atoms, the surface structure is similar to that of the corresponding bulk planes, with only a small amount of relaxation in the surface layers as determined by LEED.…”
Section: A Main Features Of the Clean Surfacesupporting
confidence: 54%
“…Earlier studies of the (100) surface based on both experimental (STM, XPS, and dynamical LEED) and ab initio studies using density functional theory (DFT) have shown that the surface terminates at incomplete P layers. 16,17 The best agreement is found for the P termination models that have all 22 Al atoms per surface unit cell present, but with all 4 Co atoms per unit cell missing. Aside from these missing atoms, the surface structure is similar to that of the corresponding bulk planes, with only a small amount of relaxation in the surface layers as determined by LEED.…”
Section: A Main Features Of the Clean Surfacesupporting
confidence: 54%
“…For instance, this restructuring of the surface layer is quite different from the structure that was determined for the similar compound surface Al 13 Co 4 (100) [17]. In that case, although the topmost surface layer was also found to be the Al-dense P layer, it was essentially a simple truncation of the bulk structure with only the Co atoms missing.…”
Section: Discussionmentioning
confidence: 55%
“…In this case, the underlying F and P layers were no longer simply laterally shifted by a/2. SATLEED does not support simultaneous calculation and optimization of more than one termination, so each of the F and P terminations was optimized separately and averaged as was performed by Shin et al [17]. One concern for complex structures is to constrain the number of fitted parameters so that it does not exceed a certain number related to the size of the dataset used in the analysis.…”
Section: B Calculationsmentioning
confidence: 99%
“…However, even when comparing the two samples studied by the same technique-STM-surface structures were still clearly different. DFT confirmed that in the range of allowed chemical potential, several different surface structures were viable [44,49]. having been subjected to more cycles of sputtering and annealing than the other, before the onset of STM experiments.…”
Section: Discussionmentioning
confidence: 59%
“…Perhaps most striking is a series of studies of Al13Co4(100) [44,48,49], in which three different samples yielded three different surface structures, even though the surfaces were prepared in very similar fashion. Furthermore, the stability range of bulk Al13Co4 spans only 0.5 at%, so any differences in bulk composition must have been very small.…”
Section: Discussionmentioning
confidence: 99%